Perioperative glycemic control in patients undergoing cardiac surgery - Bednarski, Dariusz; Krzych, Łukasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2025)
Diabetes mellitus (DM) is one of the most common chronic diseases, affecting globally about 537 million adults. Cardiovascular disease remains the leading cause of death and medical emergencies in the DM patient population. As a result, about 40% of patients with DM undergo cardiac surgery, mainly in the coronary arteries. Uncontrolled hyperglycemia, especially the prolonged condition, is an independent factor in postoperative mortality and the cause of many serious complications, such as surgical wound infection, sepsis, renal failure or cerebral or cardiovascular incidents. Adequate glycemic control in the perioperative period is the most important way to prevent the above complications. The issue has remained an important topic of many observational and experimental studies for years. This paper summarizes the current knowledge with regard to strategies of hyperglycemic control in patients undergoing cardiac surgery.